Prevalence of dental caries in Hadrianapolis medieval population (X. century) (Bulletin of the International Association for Paleodontology, 2021)
Dental caries has been one of the major oral health problems of the human race since the Stone Age. Herbal remedies were used during the Neolithic period. The skeletal remains found during the archeological excavations in Hadrianapolis region by Edirne Museum during 2002-2003 were linked to Eastern Roman-Byzantium period. Thirty seven skeletal remains out of total 139 were studied. The aim of this study was to determine the number of teeth with cavities and the prevalence of dental caries in the skeletal remains of Hadrianapolis inhabitants from X. century using the DMFT index.